Hibridisasi Heavy Metal dan Islam: Tranformasi Band Metal Sebagai Lahirnya Metal Islam di Indonesia - Sujudi, Anis (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2020)
This paper aims to analyze the hybridition of heavy metal and Islam through Islamic metal in Jakarta, Bandung and several other places in Indonesia, which have changed the metal scene in Indonesia. This paper uses a descriptive discussion with qualitative methods and concepts of hybridization and cosmopolitanism. The results of this study indicate, Islamic metal occurs, because of the low conflict between government, Islam and metal. The presence of Islamic metal in the metal scene changes community patterns, habits and identity in metal, by applying values based on Islam. The existence of Islamic metal as a new sub-genre incites the pros and cons of Islam and the metal scene, because it considers the phenomenon of exclusivity in inclusiveness in metal.